2015
DOI: 10.4028/www.scientific.net/amr.1129.209
|View full text |Cite
|
Sign up to set email alerts
|

Use of Polishing Alumina as Flame Retardant in Orthophthalic Polyester Resin Matrix Composites

Abstract: The field of Civil Engineering Materials has found a use for a range of industrial waste products as substitutes, that are as effective as standard construction materials but which have the bonus of providing an ecologically sound alternative for materials that would otherwise become an environmental concern. The use of waste materials in polymer composites is a prime example of this practice. These composites display excellent mechanical properties but must be adapted to the combustibility properties. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Niaki et al [36] reported that adding crushed basalt aggregates into PC led to decreases in the highest maximum stress rapidly, but increases the yield displacement significantly due to temperature increase. Gorninski et al [53] produced PC composites using waste alumina and showed that the addition of alumina flame retardant waste can efficiently improve the temperature resistance of the PC.…”
mentioning
confidence: 99%
“…Niaki et al [36] reported that adding crushed basalt aggregates into PC led to decreases in the highest maximum stress rapidly, but increases the yield displacement significantly due to temperature increase. Gorninski et al [53] produced PC composites using waste alumina and showed that the addition of alumina flame retardant waste can efficiently improve the temperature resistance of the PC.…”
mentioning
confidence: 99%